2012
DOI: 10.1021/es302935e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Oxidative Debromination of Decabromodiphenyl Ether by TiO2-Mediated Photocatalysis in Aqueous Environment

Abstract: Direct evidence was first demonstrated for the oxidative degradation of decabromodiphenyl ether (BDE209) in aqueous TiO(2) dispersions under UV irradiation (λ > 340 nm). BDE209 was hardly debrominated over TiO(2) in UV-irradiated acetonitrile dispersions, but the addition of water into the dispersions greatly enhanced its photocatalytic oxidative debromination. The debromination efficiency of BDE209 as high as 95.6% was achieved in aqueous TiO(2) dispersions after 12 h of UV irradiation. The photocatalytic oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(25 citation statements)
references
References 38 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…This increase was mainly caused by the large surface area of the NPs. The absorption behaviors of nano-TiO 2 include physical and chemical absorption Huang et al, 2013). The absorption experiment further indicated that nano-TiO 2 has a strong absorption capability for the higher surface of nano-TiO 2 .…”
Section: Discussionmentioning
confidence: 90%
“…This increase was mainly caused by the large surface area of the NPs. The absorption behaviors of nano-TiO 2 include physical and chemical absorption Huang et al, 2013). The absorption experiment further indicated that nano-TiO 2 has a strong absorption capability for the higher surface of nano-TiO 2 .…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, we also measured the bioconcentration of nano-TiO 2 (as Ti) in the larvae. The increased bioconcentration of BDE-209 in the presence of nano-TiO 2 could be attributed to the adsorption of organic contaminants due to the large surface area of the NPs; the sorption behaviors of nano-TiO 2 include physical sorption through electrostatic forces and chemical sorption (Huang et al, 2013;Tan et al, 2012). The adsorption experiment further indicated that nano-TiO 2 has a stronger adsorption capability for BDE-209.…”
Section: Discussionmentioning
confidence: 93%
“…However, applications for another important emerging pollutant's category like flame retardants have been investigated in a lesser extent. The existing studies are focused mainly on tetrabromobisphenol A and other polybrominated diphenyl ethers (PBDEs) [29][30][31][32][33] whereas for organophosphorus flame retardants (OPFRs), which have replaced the banned PBDEs, the data are very scarce [34]. OPFRs are extensively used in various different applications [35,36] and they can migrate from the host materials into surrounding environmental media relatively easily by volatilization, leaching and/or abrasion due to the non-chemically bonded incorporation for many of them in the material matrices [36].…”
Section: Introductionmentioning
confidence: 99%